Design and construction of an innovative brain phantom prototype for MRI. Issue 2 (17th September 2018) - Altermatt, Anna; Santini, Francesco; Deligianni, Xeni; Magon, Stefano; Sprenger, Till; Kappos, Ludwig; Cattin, Philippe; Wuerfel, Jens; Gaetano, Laura
Abstract : Purpose: The purpose of this project was to construct a physical brain phantom for MRI, mimicking structure and T1 relaxation properties of white matter (WM) and gray matter (GM). Methods: The phantom design comprised 2 compartments, 1 resembling the WM and 1 resembling the GM. Their T1 relaxation times, as assessed using an inversion recovery turbo spin echo sequence, were reproduced using an agar gel doped with contrast agent (CA) and their folding patterns were simulated through a molding‐casting procedure using 3D‐printed casts and flexible silicone molds. Three versions of the assembling procedure were adopted to build: Phantom1 without any separation; Phantom2 with a varnish layer; and Phantom3 with a thin wax layer between the compartments. Results: Phantom1 was characterized by an immediate diffusion of CA between the 2 compartments. Phantom2 and Phantom3, instead, showed relaxation times and shape comparable with the target ones identified in a healthy control subject (WM: 754 ± 40 ms; GM: 1277 ± 96 ms). Moreover, both compartments revealed intact gyri and sulci. However, the diffusion of CA made Phantom2 stable only for a short period of time. Phantom3 showed stability within a time window of several days but the wax layer between the WM and GM was visible in the MRI. Conclusion: Structural and intensity properties of the constructed phantoms are useful in evaluating and validating steps from image acquisition to image processing. Moreover, the described constructing procedure and its modular design make it adjustable to a variety of applications.